Sagot :
Answer
Find the value of the variable in each equation.
x + 7 = 15
x = 15 - 7
x = 8
x-9 = 12
x = 12 + 9
x = 21
Y - 8 = 23
Y = 23 + 8
Y = 31
b + 15 = 18
b = 18 -15
b = 3
3m + 4 = 16
3m = 16 - 4
3m = 12
m = 12/3
m = 4
2a-5=11
2a = 11 +5
2a = 16
a = 16/2
a = 8
9-x=3
-x = 3-9
-x = -6
x = 6
2+3n=11
3n = 11 -2
3n = 9
n = 9/3
n = 3
9-x= 3
-x = 3 -9
-x = -6
x = 6
8+ y = 12
y = 12 - 8
y = 4
2b + 7 = 31
2b = 31 -7
2b = 24
b = 24/2
b = 12
9m-4=14
9m = 14 + 4
9m = 18
m = 18/9
m = 2
7m - 32 = 24
7m = 24 + 32
7m = 56
m = 56/7
m = 8
3x-19=26
3x = 26 + 19
3x = 45
x = 45/3
x = 15
Hope it helps
Find the value of the variable in each equation.
x + 7 = 15
x = 15 - 7
x = 8
x-9 = 12
x = 12 + 9
x = 21
Y - 8 = 23
Y = 23 + 8
Y = 31
b + 15 = 18
b = 18 -15
b = 3
3m + 4 = 16
3m = 16 - 4
3m = 12
m = 12/3
m = 4
2a-5=11
2a = 11 +5
2a = 16
a = 16/2
a = 8
9-x=3
-x = 3-9
-x = -6
x = 6
2+3n=11
3n = 11 -2
3n = 9
n = 9/3
n = 3
9-x= 3
-x = 3 -9
-x = -6
x = 6
8+ y = 12
y = 12 - 8
y = 4
2b + 7 = 31
2b = 31 -7
2b = 24
b = 24/2
b = 12
9m-4=14
9m = 14 + 4
9m = 18
m = 18/9
m = 2
7m - 32 = 24
7m = 24 + 32
7m = 56
m = 56/7
m = 8
3x-19=26
3x = 26 + 19
3x = 45
x = 45/3
x = 15
Hope it helps